Performansi Purifikasi Biogas Dengan KOH Based Absorbent - Hermawan, Dadang; Hamidi, Nurkholis; Sasongko, Mega Nur (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2016)
The absorpstion of CO2 is aimed to increase the methane gas fraction in biogas. Enhancing methane fraction hopefully will increase the total energy of the biogas it self. The purification process of biogas minimizing another elements maintains combustion, especially minimizing H2O, CO2, and H2S. The purification using KOH as the absorbent to decrease the CO2. The result shown that the content of CO2 decreased into 27% from 35.5%, the average content of CH4 increased from 18% to 48.5%. Increasing KOH composition decreases bubble generator diameter and mass flow.